Uma análise do aspecto educacional do Programa Bolsa Família na União da Vila Nova/Vila Nair, bairro do município de São Paulo - Santos, Danielle de Sousa (2010)
Whereas the emphasis in the public policy of the Programa Bolsa Família as a way to combat poverty, also considering the governmental discourse, according to which, education is a key element for social inclusion, considering that the Programa Bolsa Família is a public policy that assumes that access to education and staying in school would enable the social inclusion of families served, this paper aims to analyze the Bolsa Família implemented by Law 10.836/04, to identify the effects of the program in its educational aspect intended, or that is, access to education and school attendance of the children and youth served as a means of social inclusion. To this end we analyzed the rates of absences and academic achievement of students from 8th grade at a school in Sao Paulo State, located in União Vila Nova/Vila Nair, District Jacuí, at the East Zone, a region with the lowest IDH-M of São Paulo. In addition, we conducted interviews with four mothers selected from the income of children; two with good school performance, two with low school performance. Here, we used as the main theoretical base, the contributions of Bourdieu, Lahire and Charlot, referring to exclusion from school, viewed from the perspective of school failure. For this analysis we resort to an empirical and qualitative data obtained through documentary analysis of records of children school data and interviews transcript